Towards a robust and versatile method for monitoring E-modulus of concrete since casting: enhancements and extensions of EMM-ARM - Granja, José Luís Duarte (2017)
In face of the importance of assessing mechanical properties of cement‐based materials since early ages, as well as the known limitations of existing methods, the EMM‐ARM (Elasticity Modulus Measurement through Ambient Response Method) was initially proposed in 2009. Since its first application, this method has been under constant development and extension to the study of other materials such as stabilized soils or epoxy resins. Extensive use has revealed several limitations on robustness and versatility that are addressed through a set of improvements proposed in this paper. Such improvements attempt to make EMM‐ARM more appropriate for systematic applications both in laboratory and in situ environments. These objectives were achieved through the application of a new test mould material, redesigned support systems, and the development of a new reusable mould. Additionally, the use of a small excitation applied to the beam to decrease the sensitivity of the method to the environmental noise was assessed.